DETERMINAN INTEGRITAS LAPORAN KEUANGAN - Widyaningsih Azizah (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2022)
This study aims to empirically examine the effect of firm size, leverage, managerial ownership, and institutional ownership to the integrity of financial statements on manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange during 2018-2019. The data used is secondary data. The sample used in this study were 19 manufacturing companies in the basic and chemical industrial sectors. Samples were obtained using purposive sampling method. This research was conducted using multiple linear regression analysis with Eviews10 application software. The results show that firm size, leverage, managerial ownership, and institutional ownership affect the integrity of financial statements on manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange.